2019
DOI: 10.1186/s43055-019-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of hepatic and cardiac iron burden in pediatric thalassemia major patients: spectrum of findings by T2*

Abstract: Background: Iron deposition distorts the local magnetic field exerting T2* signal decay. Biopsy, serum ferritin, echocardiography are not reliable to adjust iron chelation therapy. Quantified MRI signal decay can replace biopsy to diagnose iron burden, guide treatment, and follow up. The objective of this study is to evaluate the role of T2* in quantification of the liver and heart iron burden in thalassemia major patients. This cross-sectional study included 44 thalassemia patients who were referred to MRI un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…ese finding were also found in Jordan; a positive correlation between serum ALT and AST concentrations and serum ferritin levels in beta-thalassemia patients compared to controls was found [31]. Previous studies conducted in children and adolescences showed correlation between liver T2 * MRI and serum ferritin, as well as liver enzymes [11,17]. However, in this study, only similar trends were found although not reaching statistical significance, probably because of the small sample sizes, which affect the power of analysis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…ese finding were also found in Jordan; a positive correlation between serum ALT and AST concentrations and serum ferritin levels in beta-thalassemia patients compared to controls was found [31]. Previous studies conducted in children and adolescences showed correlation between liver T2 * MRI and serum ferritin, as well as liver enzymes [11,17]. However, in this study, only similar trends were found although not reaching statistical significance, probably because of the small sample sizes, which affect the power of analysis.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, the correlation between cardiac T2 * MRI and serum ferritin was not strong. Similarly, other studies also found weak or no correlation between cardiac T2 * and serum ferritin [11,17]. It indicated the importance of cardiac T2 * MRI to be routinely screened to detect cardiac overload.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Shehata et al. 14 reported a weak but significant correlation between the hepatic and cardiac T2* time. In our study, there was no significant correlation between these times, which can be explained by the small number of patients in our study.…”
Section: Discussionmentioning
confidence: 98%
“…However, there was no statistically significant influence of lower ferritin levels on the cardiac and liver T2* times, suggesting that manifestations of the effect of iron overload on the myocardium and liver parenchyma can require more than 1 year. Shehata et al 14 reported a weak but significant correlation between the hepatic and cardiac T2* time. In our study, there was no significant correlation between these times, which can be explained by the small number of patients in our study.…”
Section: Discussionmentioning
confidence: 98%